(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
This scientific article analyzes the history, developmental stages, and theoretical foundations of the art of maqom, our national musical heritage, which has been formed over the centuries in Uzbekistan and Central Asia. The inextricable connection of maqom with music theory, philosophy, and performing traditions is scientifically substantiated. This article focuses on research conducted by musicologists